SYSTEMATIZATION AND ANALYSIS OF DATA IN EDUCATION: CONTRIBUTIONS OF DIGITAL TOOLS IN THE WORK OF THE EDUCATIONAL COUNSELOR (Editora Impacto Científico, 2025)
The study aims to analyze how digital tools can contribute to the systematization and analysis of data in the school environment, in order to optimize the intervention of the educational advisor in the face of the challenges imposed by the contemporary school. The methodology adopted consisted of a qualitative bibliographic study. To this end, publications from the last five years on the topic in question were selected. The study analyzes the process of historical evolution and the redefinition of the role of the educational advisor in the Brazilian educational context, from its legal regulation to the challenges imposed by contemporary educational demands, where this professional has become the essential agent in promoting an education focused on the integral development of the student. It also addresses how digital tools can offer new possibilities for this professional, who has increasingly become a mediator of pedagogical processes. The use of digital tools in the systematization of school data represents a significant advance in the modernization and efficiency of pedagogical and administrative processes in the educational environment. In addition to strengthening integration between school and family, these tools also enhance the intervention actions of the educational counselor, especially in mediating sensitive issues, promoting active listening and student protagonist. Throughout this study, it was evident how these technologies enhance the work, promoting more integrated management, guided by concrete data and facilitating informed and assertive decision-making. The conscious and reflective incorporation of these tools is therefore an indispensable path towards the modernization of educational practice, in order to respond to the demands and challenges imposed by the digital society.